2021
DOI: 10.1021/acsami.1c12412
|View full text |Cite
|
Sign up to set email alerts
|

A Dopamine Acrylamide Molecule for Promoting Collagen Biomimetic Mineralization and Regulating Crystal Growth Direction

Abstract: The reconstruction of the intra/interfibrillar mineralized collagen microstructure is extremely important in biomaterial science and regeneration medicine. However, certain problems, such as low efficiency and long period of mineralization, are apparent, and the mechanism of interfibrillar mineralization is often neglected in the present literature. Thus, we propose a novel model of biomimetic collagen mineralization that uses molecules with the dual function of cross-linking collagen and regulating collagen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…To stabilize the initial environment, the specimens were held at 20 °C for 5 min. They were then heated at 5 K·min −1 to 800 °C under a nitrogen atmosphere (20 mL·min −1 ) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To stabilize the initial environment, the specimens were held at 20 °C for 5 min. They were then heated at 5 K·min −1 to 800 °C under a nitrogen atmosphere (20 mL·min −1 ) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…When the direction of the collagen fibers’ long axis was parallel to the longitudinal sections, the HA crystals appeared as a line that was bundled together of intrafibrillar and interfibrillar (Fig. 3 D; yellow double-headed arrows indicate the HA crystals arrangement direction) [ 25 ]. When the direction of the collagen fibers was perpendicular or at a certain angle to the longitudinal sections, the HA crystals appeared as dots that were bundled together by the intrafibrillar and interfibrillar (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research has shown that mussel adhesive protein may inhibit MMP activity and facilitate dentin adhesion [ 23 ], and a DOPA derivative of N-2-(3,4-dihydroxylphenyl) acrylamide (DAA) was designed and synthesized (Fig. S1 ) to effectively bind collagen; improve cross-linking degree, thermal stability, resistance to enzymatic hydrolysis, and mechanical properties of collagen; and also induce collagen intra- and interfibrillar mineralization [ 24 , 25 ]. In addition, DAA has an amide (–CO–NH–) group, which differs from the ester group (–CO–O–R–) in traditional acrylate and methacrylate adhesive monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the adhesion chemistry of marine mussels, various hydrogels formed by derivatives with catechol groups have wide application prospects in tissue engineering scaffolds [ 21 , 22 ]. Studies indicate that catechol groups have a strong affinity for various organic and/or inorganic surfaces and biomacromolecules that can improve hydrogels’ mechanical properties [ 23 , 24 , 25 ]. As catechol and amino acids derivatives, dopamine (DA) has good adhesion and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%